1999
DOI: 10.1046/j.1440-1754.1999.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Does postoperative ventilation have an effect on the integrity of the anastomosis in repaired oesophageal atresia?

Abstract: Several authors have claimed that the use of postoperative ventilation or graded withdrawal of respiratory support reduces the incidence of anastomotic complications after repair of oesophageal atresia, particularly where the gap between the oesophageal ends has been extensive or where the anastomosis has been constructed under tension. Careful review of their data reveals little objective evidence to either support or refute this contention. Many institutions are achieving low leakage rates following oesophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…[ 6 ] They also reported an increased incidence of all complications with increasing gap length in a series of 66 neonates and proposed that a classification based on gap length was more relevant in the modern era. [ 6 ] Our long gap patients also had much higher requirement of postoperative ventilation similar to the findings of Beasley[ 8 ] and Uchida et al . [ 9 ] The importance of gap length on the final outcome in EA patients have been well stressed by Upadhyaya et al .…”
Section: Discussionsupporting
confidence: 86%
“…[ 6 ] They also reported an increased incidence of all complications with increasing gap length in a series of 66 neonates and proposed that a classification based on gap length was more relevant in the modern era. [ 6 ] Our long gap patients also had much higher requirement of postoperative ventilation similar to the findings of Beasley[ 8 ] and Uchida et al . [ 9 ] The importance of gap length on the final outcome in EA patients have been well stressed by Upadhyaya et al .…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, we suggest that higher respiratory problems in IV group may relate with ventilation strategy and may not affected by these parameters. The issue of chest tube placement after the operation is also a controversial issue, and our results showed that the majority of patients in both groups had chest tubes inserted 13 …”
Section: Discussionmentioning
confidence: 70%
“…The issue of chest tube placement after the operation is also a controversial issue, and our results showed that the majority of patients in both groups had chest tubes inserted. 13 After EA repair, patients may receive elective respiratory support to eliminate probable anastomotic complications by decreasing the tension on esophageal anastomosis. In addition, concomitant patient-related risk factors such as prematurity and lung-related respiratory tract problems may result in a respiratory support requirement.…”
Section: Spitz Et Al Recommended That Patients With Tensioned Anasto-mentioning
confidence: 99%
“…Several authors have described the use of PEVS under paralysis with neck flexion after repair of EA for the purpose of reducing anastomotic complications by decreasing anastomotic tension [1,3,5,6]. In Japan, many medical institutes have supported the efficacy of this postoperative management of EA.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated postoperative elective ventilatory support (PEVS) reduces anastomotic complications by decreasing anastomotic tension [1,3,5,6].…”
Section: Introductionmentioning
confidence: 99%